2011
DOI: 10.1161/strokeaha.111.620112
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Traumatic Brain Injury

Abstract: Background and Purpose-Previous studies have identified an array of morbidities following traumatic brain injury (TBI), including certain neurological disorders. However, no direct evidence has been reported on the link between TBI and stroke. This population-based study was designed to estimate the risk of stroke during a period of 5 years following a TBI, compared with individuals who did not suffer TBI during the same period. Methods-Data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 33 publications
7
83
0
Order By: Relevance
“…[24][25][26] Still, concerns about increased stroke risk (37-55% potential increase) may discourage physicians from prescribing SSRIs to older adults with TBI, especially because TBI is an independent risk factor for stroke. [39][40][41][42][43] Other factors that may influence treatment decisions among older adults after TBI include post-TBI cognitive impairment, polypharmacy, and altered drug metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Still, concerns about increased stroke risk (37-55% potential increase) may discourage physicians from prescribing SSRIs to older adults with TBI, especially because TBI is an independent risk factor for stroke. [39][40][41][42][43] Other factors that may influence treatment decisions among older adults after TBI include post-TBI cognitive impairment, polypharmacy, and altered drug metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that TBI is associated with increased risk of stroke [10][11][12]. Although the actual mechanism is still not completely understood, several hypotheses have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in several studies TBI was found to be associated with increased risk of [10][11][12]. Because stroke results from disturbance of the blood supply to the brain, it has been hypothesized that vascular damage from TBI may also induce stroke in survivors [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the risk of hemorrhagic strokes after traumatic brain injuries was demonstrated epidemiologically [23] but they are considered risky only after some weeks and this patient’s brain CT showed a typical hemorrhagic stroke with no evidence to suggest a traumatic brain injury.…”
Section: Case Presentationmentioning
confidence: 98%